NAPOLEOŃSKI GARNIZON GŁOGOWSKIEJ TWIERDZY W LATACH 1812-1814 - Helwig, Jarosław (In Gremium. Studies in History, Culture and Politics, 2014)
Napoleonic Garrison of the Fortress of Głogów in the Years 1812-1814 During the Napoleonic wars, the fortress of Głogów played an important role in the plans of both fighting parties. Its seizure in December 1806 enabled to unite safely the troops remaining under the command of Jerome Bonaparte (so-called allied army, consisting of Bavarian and Wurttembergian units – later 9th Corps) with the main forces operating in Poland. After terminating military operations, the problems with paying off the contribution dictated to Prussia in Tilsit made Głogów, together with Szczecin and Kostrzyn, remain in the French hands, and the maintenance of the fortress of Głogów was assigned to the Prussians, which caused additional expenditures. These were substantial sums, as the garrison initially comprised of 2,500 people, but till the end of November 1808, their number rose to 4,200 people (including 900 sick). The line-up of the Napoleonic troops garrisoned in the fortress was constantly changing. At the initial stage of the occupation soldiers from the troops of prince Jerome, who had seized the fortress in December 1806, were at service. Later they got replaced by the French. Since March 1809, in the place of the French infantry and cavalry there came Polish detachments of cavalry and Saxon soldiers. This situation sustained until the middle of the year 1812 (the Russian campaign). Since that moment up to the end of 1812, French soldiers remained the major force in the fortress. When in December 1812 the army of Napoleon was retreating, the significance of the fortress of Głogów started rising. It was decided that the reconstruction of the 3rd Cavalry Corps and light brigades of the cavalry of 4th and 6th Corps, coming back from the Russian campaign, was to be conducted there. The city also began the preliminary preparations for the defense against the approaching enemy. The core of the new garrison was to consist of the Italian 4th Corps infantry. During the first blockage and siege in 1813, the garrison of the fortress, except the French, were also the Croatians, the Saxons, the Dutch, the Spanish and the Badenians (during the second one the main defending force was the infantry soldiers of the 151 line regiment, while the Badenian soldiers were relieved by the soldiers from Frankfurt-am-Main). The battle for Głogów was prolonging, and the fortress gave in only in April 1814, eleven days after the surrender of Paris and the abdication of Napoleon.